Correlation between organizational support, self-efficacy, and core competencies among long-term care assistants: a structural equation model - Liu, Ankang; Wang, Dong; Xu, Shanshan; Zhou, Yixia; Zheng, Yao; Chen, Juan; Han, Biyuan (Frontiers in Psychology, 2024)
Introduction Long-term care assistants are taking on more important roles in the healthcare system. The purpose of this study was to investigate what demographic factors influence the core competencies of nursing assistants, as well as to investigate the levels of organizational support, self-efficacy, and core competencies among nursing assistants in China, to explore the relationship between them. Methods This is a cross-sectional study with prospective data collection based on a self-report questionnaire. A total of 320 long-term care assistants from two healthcare institutions. We collected socio-demographic characteristics and measured their perceived organizational support, self-efficacy, and core competency levels of the participants. Pearson correlation tests were conducted to examine the relationships among three variables, and a structural equation model was developed to test the interrelationships among these variables. Results The results indicated that age, employment type, licensing status, monthly income, pre-job training, and training methods were associated with core competency, with nursing knowledge identified as a weak area in core competencies. There were significant associations among each dimension of perceived organizational support, self-efficacy, and core competencies (P < 0.01). The structural equation model demonstrated good fit: X2/df= 2.486, GFI=0.974, CFI= 0.988, IFI=0.988, TLI=0.977, RMSEA=0.068, SRMR=0.013. The direct effect of organizational support on core competencies was 0.37, with self-efficacy mediating the relationship between organizational support and core competencies, yielding an indirect effect of 0.122 and a total effect coefficient of 0.492 (all P < 0.001). Conclusions Training in core competencies should prioritize nursing knowledge. Enhanced perceived organizational support and self-efficacy among nursing assistants were associated with higher core competencies.